2022
DOI: 10.1038/s41598-022-13535-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiome of sacbrood virus-resistant and -susceptible Apis cerana from South Korea

Abstract: Honey bees are important pollinators for the conservation of the ecosystem and agricultural products and provide a variety of products important for human use, such as honey, pollen, and royal jelly. Sacbrood disease (SD) is a devastating viral disease in Apis cerana; an effective preventive measure for SD is urgently needed. In this study, the relationship between the gut microbiome of honey bees and SD was investigated by pyrosequencing. Results revealed that sacbrood virus (SBV)-resistant A. cerana strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Further characterization showed that larvae and pupae have a few core bacteria in their gut. This was consistent with previous reports showing that the core bacteria are relatively rare in larvae; however, they consist of highly variable communities dominated by non-core environmental bacteria [ 6 , 28 ]. Indeed, in this study, the microbiota of larvae was predominant by L. kunkeei , M. plutonius , Lactobacillus_uc , Commensalibacter, whereas those in pupae were B. subtilis , S. pruni , Lachnospiraceae .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Further characterization showed that larvae and pupae have a few core bacteria in their gut. This was consistent with previous reports showing that the core bacteria are relatively rare in larvae; however, they consist of highly variable communities dominated by non-core environmental bacteria [ 6 , 28 ]. Indeed, in this study, the microbiota of larvae was predominant by L. kunkeei , M. plutonius , Lactobacillus_uc , Commensalibacter, whereas those in pupae were B. subtilis , S. pruni , Lachnospiraceae .…”
Section: Discussionsupporting
confidence: 93%
“…Adult workers have a relatively diverse set of bacteria in their gut compared with larvae and pupae. The gut microbiota of A. cerana adult workers consisted of nine bacterial species, which was consistent with our recent studies on the gut microbiota of Vietnamese A. cerana [ 16 ] and the previous reports that the gut microflora of workers ( A. melifera and A. cerana ) may contain from five to nine taxa belonging to four phyla, including Firmicutes , Actinobacteria , Proteobacteria , and Bacteroidetes [ 1 , 2 , 12 , 16 , 17 , 18 , 28 ]. However, the composition and the abundance of predominant bacteria groups varied due to geographical differences and natural conditions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations